Butterflies on Carmen Street = Mariposas en la calle Carmen - Ward, April; Ventura, Gabriela Baeza (Piñata Books, 2007)
While she and her classmates wait for the caterpillars they are raising to be transformed into Monarch butterflies, Julianita's grandfather tells her about the annual migration of these butterflies to his hometown in Mexico.